2002
DOI: 10.1046/j.1365-4362.2002.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological observations of cutaneous tuberculosis in Larkana, Pakistan

Abstract: The observed number of patients was moderately large, thus indicating a high incidence of cutaneous tuberculosis in Larkana. Lupus vulgaris, a form of cutaneous tuberculosis, was widespread in this area and prevalent in adults, while scrofuloderma was prevalent in children. Moreover, the existing rate of the disease was higher in children aged under 10 years and lower in adults. This indicates that children are more prone to this disease than adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 26 publications
7
37
1
13
Order By: Relevance
“…Abdul Mamen and Seneha et al in their studies conducted on cutaneous tuberculosis found lupus vulgaris is the commonest form of cutaneous tuberculosis, while scrofuloderma was prevalent in children. 15,16 Granuloma with vasculitis contributes a minor group of granulomatous dermatoses. They are characterized by inflammatory cells in the vessel wall, endothelial reaction, thrombus formation and fibrin deposition ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Abdul Mamen and Seneha et al in their studies conducted on cutaneous tuberculosis found lupus vulgaris is the commonest form of cutaneous tuberculosis, while scrofuloderma was prevalent in children. 15,16 Granuloma with vasculitis contributes a minor group of granulomatous dermatoses. They are characterized by inflammatory cells in the vessel wall, endothelial reaction, thrombus formation and fibrin deposition ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Lupus vulgaris represents the most common form of cutaneous tuberculosis in Pakistani children and primarily affects the head and neck 1. It may occur following direct inoculation or endogenous spread,2 presenting as a soft painless nodule with a red-brown ‘apple jelly’ appearance on diascopy.…”
Section: Discussionmentioning
confidence: 99%
“…It is a serious public health problem in developing countries (5). Along with the inereased frequency of pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%